Two and Three-Revolution Cyclical Surfaces - Tatiana Olejnikova (Communications - Scientific letters of the University of Zilina, 2008)
The creation of two-revolution and three-revolution cyclical surfaces is presented in the paper. Classification and vector equations of the surfaces are given. The surfaces are created by translation of the circle along the curves and its centre is on the curve. The curves are created by revolution of a point about any edge of the trihedron of the previous curve and this trihedron moves simultaneously along this curve. All specific forms of surfaces are illustrated in figures visualized in Maple.